2012
DOI: 10.1002/pon.3056
|View full text |Cite
|
Sign up to set email alerts
|

Prescription patterns for psychotropic drugs in cancer patients; a large population study in the Netherlands

Abstract: A total of 113 887 cancer patients and 121 395 control subjects were included. Cancer patients were significantly more often prescribed psychotropic drugs (adjusted OR: benzodiazepines = 1.70, CI = 1.67-1.74; antidepressants = 1.38, CI = 1.34-1.42; and antipsychotics = 1.70, CI = 1.62-1.77). Lower socio-economic status, immigrant, and premorbid chronic medical conditions were significantly associated with higher risk of psychotropic use. Odds for a new prescription for all three psychotropic drugs were signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
69
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(78 citation statements)
references
References 34 publications
5
69
4
Order By: Relevance
“…The prevalence of antidepressant prescription in cancer patients was about 7.8% in this study, which was much lower than the finding of our previous study based on a database from the Netherlands (Ng et al, 2013a). Again, the low prescription rate could attributed to the under-diagnosis of depression and the high caution level in prescribing psychotropic drugs to cancer patients in the local setting.…”
Section: Discussioncontrasting
confidence: 54%
“…The prevalence of antidepressant prescription in cancer patients was about 7.8% in this study, which was much lower than the finding of our previous study based on a database from the Netherlands (Ng et al, 2013a). Again, the low prescription rate could attributed to the under-diagnosis of depression and the high caution level in prescribing psychotropic drugs to cancer patients in the local setting.…”
Section: Discussioncontrasting
confidence: 54%
“…This study also found cancer patients who were prescribed antidepressants were more likely to be younger, female, and have a diabetic, cardiovascular, or pulmonary co-morbid condition [253], while among breast cancer patients in Wisconsin, antidepressant use was more likely among women who were younger, premenopausal, obese, have fewer children, and receive adjuvant therapy in comparison to those women who did not take antidepressants [11]. Interestingly, another study among breast cancer patients found age, education, stage at time of diagnosis, time since diagnosis, or time since last recurrence or metastasis were not associated with antidepressant prescription rates [255].…”
Section: Antidepressant Usementioning
confidence: 59%
“…Antidepressants are used more frequently in the cancer population in comparison to the general population [10,253]. According to a study conducted in Australia, antidepressant use in the cancer population ranged from 6.2% to 11.7% for the different periods studied, while antidepressant use in individuals without a cancer diagnosis ranged from 4.6% to 7.4% [10].…”
Section: Antidepressant Usementioning
confidence: 99%
See 1 more Smart Citation
“…A previous study showed that shortly before dying the chances for prescription of a new psychotropic drug increase. 39 It can now be added that the increased incidence of psychiatric comorbidity and the use of psychotropic drugs are related to the terminal disease phase and are not disease specific.…”
Section: Discuss This Articlementioning
confidence: 99%